BUSINESS TOURISM INDUSTRY IN ROSTOV REGION: CURRENT DEVELOPMENT TRENDS - Nikolay D. ELETSKY; Natalia N. MOROZOVA (Advanced Engineering Research)
The results of current trends and tendencies of business tourism development in Rostov region are presented, the role of business tourism for tourist industry system performance is defined on the world, national and regional levels.